The morning news - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2002)
Do you want everyone in your organisation to be up-to-date on the latest agricultural news? See if you can adapt this simple but smart practice developed over the last fifteen months by the Office of Information and Communication section of Fiji s...